Bridging the AI Talent Gap in Supply Chain Management: Opportunities for Collaboration - Babatunde, Oyeyemi Bamidele; Okoji, Chukwudinma Taiwo; Olanihun, Zechariah Sunday; Daniel, Henry Amos (NIU Journal of Humanities, 2025)
The integration of Artificial Intelligence (AI) into supply chain management has become a key driver of operational efficiency, optimization, and innovation. However, the effective deployment of AI technologies is constrained by a significant talent gap, as the demand for AI-skilled professionals far exceeds the current supply. This gap is particularly pronounced in the supply chain sector, where specialized knowledge in both AI and supply chain operations is essential. Bridging this talent gap is crucial for industries aiming to leverage AI for competitive advantage, yet achieving this requires a collaborative approach involving multiple stakeholders. This explores the opportunities for collaboration between industry, academia, and public-private partnerships to address the AI talent shortage in supply chain management. By examining the challenges faced by organizations in recruiting and retaining AI professionals, this highlights the critical need for educational initiatives that focus on the intersection of AI and supply chain management. Industry-academia partnerships play a pivotal role in developing curricula that prepare the next generation of talent, while also fostering internship and mentorship programs to facilitate hands-on experience. Public-private collaborations can further enhance workforce development through funding and policy support aimed at AI education and training. Additionally, this discusses the importance of upskilling and reskilling existing employees, providing accessible training programs to build AI expertise within the current workforce. It also explores the potential of cross-industry knowledge sharing, global talent pool access, and promoting diversity and inclusion in AI roles. The review concludes by emphasizing the need for strategic investment in AI talent development and the importance of creating an inclusive and sustainable ecosystem to bridge the AI talent gap and accelerate the adoption of AI in supply chain management. Keyword: Bridging, AI, Talent gap, Supply chain management, Review